Effect of Altitude on Volatile Organic and Phenolic Compounds of Artemisia brevifolia Wall ex Dc. From the Western Himalayas - Nataraj, Nandita; Hussain, Manzoor; Ibrahim, Mohd; Hausmann, Alexander E.; Rao, Srinivas; Kaur, Satwinderjeet; Khazir, Jabeena; Mir, Bilal Ahmad; Olsson, Shannon B. (Frontiers in Ecology and Evolution, 2022)
Adaptation to changing environmental conditions is a driver of plant diversification. Elevational gradients offer a unique opportunity for investigating adaptation to a range of climatic conditions. The use of specialized metabolites as volatile and phenolic compounds is a major adaptation in plants, affecting their reproductive success and survival by attracting pollinators and protecting themselves from herbivores and other stressors. The wormseed Artemisia brevifolia can be found across multiple elevations in the Western Himalayas, a region that is considered a biodiversity hotspot and is highly impacted by climate change. This study aims at understanding the volatile and phenolic compounds produced by A. brevifolia in the high elevation cold deserts of the Western Himalayas with the view to understanding the survival strategies employed by plants under harsh conditions. Across four sampling sites with different elevations, polydimethylsiloxane (PDMS) sampling and subsequent GCMS analyses showed that the total number of volatile compounds in the plant headspace increased with elevation and that this trend was largely driven by an increase in compounds with low volatility, which might improve the plant’s resilience to abiotic stress. HPLC analyses showed no effect of elevation on the total number of phenolic compounds detected in both young and mature leaves. However, the concentration of the majority of phenolic compounds decreased with elevation. As the production of phenolic defense compounds is a costly trait, plants at higher elevations might face a trade-off between energy expenditure and protecting themselves from herbivores. This study can therefore help us understand how plants adjust secondary metabolite production to cope with harsh environments and reveal the climate adaptability of such species in highly threatened regions of our planet such as the Himalayas.